Moralizatorska funkcja motywów eschatologicznych w poemacie Przeraźliwe echo trąby ostatecznej Klemensa Bolesławiusza - Tyszko, Marta (Starość i młodość w literaturze i kulturze, 2016)
The aim of this paper is to analyse the 17th century poem — The Terrifying Echo of the Last Trumpet byKlemens Bolesławiusz. The author locates this poem in the circle of the Christian eschatology, by showingeschatological motives in it. Generally the most important for the shape of this work are its didacticalfunctions. Bolesławiusz is using a lot of macabre visions. He wanted to persuade the readers into moralimprovement and help them to reach salvation.